If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -19sqrt(x) + 60 = 0 Multiply qrst * x x + -19qrstx + 60 = 0 Reorder the terms: 60 + -19qrstx + x = 0 Solving 60 + -19qrstx + x = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -19qrstx + -60 + x = 0 + -60 Reorder the terms: 60 + -60 + -19qrstx + x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -19qrstx + x = 0 + -60 -19qrstx + x = 0 + -60 Combine like terms: 0 + -60 = -60 -19qrstx + x = -60 Add '-1x' to each side of the equation. -19qrstx + x + -1x = -60 + -1x Combine like terms: x + -1x = 0 -19qrstx + 0 = -60 + -1x -19qrstx = -60 + -1x Divide each side by '-19rstx'. q = 3.157894737r-1s-1t-1x-1 + 0.05263157895r-1s-1t-1 Simplifying q = 3.157894737r-1s-1t-1x-1 + 0.05263157895r-1s-1t-1 Reorder the terms: q = 0.05263157895r-1s-1t-1 + 3.157894737r-1s-1t-1x-1
| y=7/9(-7)-7 | | 100r=40(r^2-6.25) | | -7x+36=15 | | 100r=40r(r^2+2.5) | | 0.1+2x^2=0 | | -5x+8-3x=-88 | | 8(3x-12)=88x | | 3/7x-1/6x | | -6(8+x)=18 | | -x(2x-3)=527 | | x+3.6=8 | | 5x+10(-1)=-15 | | 213a+2432b= | | (7x^2y^8z^4)(7x^2z)= | | 7(5-7x)=35 | | 312421+1242= | | -3x+5+2x=16 | | c/-6=-1 | | -3+2x+3x=7 | | .10x+.25(24-x)=4.50 | | -4x+5=7x-6 | | y=-7/10*7+7 | | -2/3x=(-8) | | 3x-5=-34-10x | | 8x/68 | | 6w^2=19w-10 | | -x+4=-4+x | | x/4+16=20 | | (6x^7)(2x^6)= | | 3/4x=(-9) | | .10+.25(24-x)=4.50 | | r/-2=(-8) |